2023
DOI: 10.47163/agrociencia.v57i5.2802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Season, Maximum Temperature and Relative Humidity on the Gestation of Tropical Milking Criollo Cows

Abstract: The season of the year (ES), maximum temperature (Tmax) and relative humidity (RH) affect gestation success of Tropical Milking criollo (TM) heifers, but their effects on the gestation of TM cows are not completely known. The study aimed to determine the effects of environmental factors along with artificial insemination (AI) service and calving on the gestation success of TM cows. Data were collected during 14 years, 959 records of AI of 155 cows in three seasons: hot-dry (HD), hot-humid (HH) and fresh-dry (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The criollo breeds Romosinuano and Tropical Milking are Bos taurus naturalized to hot climates of the tropical region, with populations established in different countries of the Americas, although relatively small of thousands of individuals [22][23][24]. Studies have been carried out to determine the effect of Tmax and RH on the fertility of TM heifers and cows,it was found that the lowest pregnancy, less than 50%, occur in the hot dry season with Tmax greater than 27 °C and RH of 85% for heifers [18], but no season effect was observed in cows [25]. When comparing, Brahman and Angus breeds to determine the effect of heat shock on oocytes cultured in vitro at 41°C, oocytes had greater cleavage, with embryos of more than eight cells four days after IVF [26].…”
Section: Introductionmentioning
confidence: 99%
“…The criollo breeds Romosinuano and Tropical Milking are Bos taurus naturalized to hot climates of the tropical region, with populations established in different countries of the Americas, although relatively small of thousands of individuals [22][23][24]. Studies have been carried out to determine the effect of Tmax and RH on the fertility of TM heifers and cows,it was found that the lowest pregnancy, less than 50%, occur in the hot dry season with Tmax greater than 27 °C and RH of 85% for heifers [18], but no season effect was observed in cows [25]. When comparing, Brahman and Angus breeds to determine the effect of heat shock on oocytes cultured in vitro at 41°C, oocytes had greater cleavage, with embryos of more than eight cells four days after IVF [26].…”
Section: Introductionmentioning
confidence: 99%